Analisis Penerapan Sistem Informasi Dan Pengendalian Internal Dalam Pembiayaan Kredit - Salma Khairunnisa; Hadi Sutomo; Abdul Roup (Institut Bisnis dan Informatika Kesatuan, 2022)
Information system is a collection of information in a database using information technology models and media used in making business decisions of a company. Internal control is a plan, method, procedure, and policy designed by management to provide adequate assurance on the achievement of operational efficiency and effectiveness, the presence of financial reporting, security of assets, compliance or compliance with laws, policies and other regulations. Credit financing is the provision of money or claims that can be negotiated with it, based on an agreement or agreement between a bank or a financing institution and another party that requires the party being financed to return the money or claim after a certain period of time with interest. The purpose of this study was to determine the role of the information system applied by PT. Sinar Mitra Sepadan Finance and to know the effect of the system on the internal control of credit financing. The result of this research shows that information system provide a very important role in a correlation with credit financing internal control. It can be seen by imformation system can avoid errors and frauds which causes loss. Keywords: information system, credit financing internal control